SELECTION OF PLANTING OF CROPS BY ROTATION USING TOPSIS METHOD - Sudha, A. Sahaya (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
This paper depicts the possibility of multiple criteria decision making methods in agricultural enterprise decisions. The success of every organization depends among other things on the ability to make the right decision.Â What is more important for making the optimal decision is the necessity to analyse the decision problem in detail from various points of view.Â This case study shows the application of the multiple attribute analysis methods in the planning and creation of crop rotation in an agricultural enterprise.Â Using entropy weight in TOPSIS method, a comprehensive evaluation is done on the development level of crops in rotation. Keywords: Entropy, TOPSIS, Multi Criteria Decision Making